NUTRITION IN AYURVEDA WITH SPECIAL REFERENCE TO NITYASEVANEEYA AND ANITYASEVANEEYA DRAVYAS - Parvathy B; Neelakanta J Sajjanar; Gopalakrishna G (International Journal of Ayurveda and Pharma Research, 2021)
It is an undeniable fact that food choices make a huge impact on health of an individual. 21st century has witnessed an increase in incidences of non-communicable chronic diseases also known as lifestyle diseases. One of the major factors responsible for it is the unhealthy food habits. Thus, it is the need of the hour to understand more about the right food choices for daily nutrition. Ayurveda explains about of nutrition under Pathyapathya. Ayurveda emphasizes the importance of Pathyapathya in the maintenance of health as well as management of diseases. Nityasevaneeya dravyas, are the food items which are ideal for regular use like green gram (Mudga), ghee (Go ghruta), honey (Madhu). These help to promote and maintain health as well as prevent diseases. At the same time Anitya sevaneeya dravyas, are those food articles which are not suitable for regular use like Paneer (Kurchika), curd (Dadhi), black gram (Masha). These food items on regular consumption can lead to many diseases. In this study a detailed review of each drug mentioned under Nitya sevaneeya and Anityasevaneeya dravyas both in Ayurveda and contemporary science are done. Review indents to highlight the scientific background behind each food article to re-establish their relevance in today’s time.